The problem of suicidal personality in current suicidology - Keturakis, V. (Psichologija, 1996)
This paper aims to examine the current state of research of suicidal personality in suicidology. Methodological precautions are discussed emphasizing the multicausal nature of the suicidal process and the processional nature of personality. Specific character traits as a high level of aggression and hopelessness, low self-integration and self-esteem, and cognitive disturbances were often found to be correlated with suicidal tendencies. Suicidal persons were considered to be weak problem solvers. Emotionally-oriented stress coping strategies and maladaptive coping and survival skills were prevalent among them. The problem of one-dimensionality of suicidological research is brought up and elaborated upon in this article. The possibility of integrating the noetic (noological) dimension of personality into suicidological surveys is suggested, emphasizing a multidimensional point of view. Future prospectives concerning the link between some other noetic phenomena such as the fear of death, the awareness of freedom and responsibility, or the experience of existential isolation and suicidal behaviour are drawn.
Keywords: suicide; personality; suicidal personality